1981
DOI: 10.1126/science.6169147
|View full text |Cite
|
Sign up to set email alerts
|

Species Restriction of a Monoclonal Antibody Reacting with Residues 130 to 137 in Encephalitogenic Myelin Basic Protein

Abstract: A monoclonal antibody (immunoglobulin G1) has been produced that reacts against myelin basic protein present in or extracted from the brains of many mammals-with certain important exceptions. Because of known species differences in amino acid sequences of basic protein and of certain peptide fragments, the binding site for this particular antibody appeared likely to include residues 130 to 137. Confirmation of this hypothesis was obtained by amino acid composition of the major immunoreactive peptides produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
1

Year Published

1983
1983
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 16 publications
0
23
1
Order By: Relevance
“…To compare the staining of IN-1 to that of certain myelin specific markers, adjacent sections were stained with IN-1 and mAbs against MBP, MOG and MAG (Sires et al, 1981;Linington et al, 1984;Poltorak et al, 1987). mAbs against MBP, MOG and MAG (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To compare the staining of IN-1 to that of certain myelin specific markers, adjacent sections were stained with IN-1 and mAbs against MBP, MOG and MAG (Sires et al, 1981;Linington et al, 1984;Poltorak et al, 1987). mAbs against MBP, MOG and MAG (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Further support for a central role of MBP is provided by the observation that immunization with MBP leads directly to the clinical and pathological condition of EAE, an in vivo model of MS [212,213]. MBP is not, however, the only potential myelin antigen, as similar arguments have been designed for the proteolipid protein [214] and lipid components (e.g.,gangliosides) [215] of myelin.…”
Section: D) Periaxinmentioning
confidence: 97%
“…The MBPs of oligodendrocytes were detected by the enhanced luminol reaction using Renaissance (Dupont NEN, Boston, MA). From the immunological aspect, the MBP monoclonal antibody (Sires et al [1981] Science 214:87–89) was revealed to recognize MBPs with molecular masses of 21.5 kDa and 18.5 kDa. Furthermore, we found that Ile‐166 in the rat 18.5‐kDa MBP isomers was replaced by methionine.…”
mentioning
confidence: 99%